The role of collective action in the provision of agri-environmental public goods: theoretical development through case studies in Italy - Vanni, Francesco <1976> (Alma Mater Studiorum - Università di Bologna, 2012)
The thesis aims at analysing the role of collective action as a viable alternative to the traditional forms of intervention in agriculture in order to encourage the provision of agri-environmental public goods. Which are the main benefits of collective action, in terms of effectiveness and efficiency, compared to traditional market or public intervention policies? What are the drivers that encourage farmers to participate into collective action? To what extent it is possible to incorporate collective aspects into policies aimed at providing agri-environmental public goods? With the objective of addressing these research questions, the thesis is articulated in two levels: a theoretical analysis on the role of collective action in the provision of public goods and a specific investigation of two local initiative,s were an approach collective management of agro-environmental resources was successfully implemented. The first case study concerns a project named “Custodians of the Territory”, developed by the local agency in Tuscany “Comunità Montana Media Valle del Serchio”, which settled for an agreement with local farmers for a collective provision of environmental services related to the hydro-geological management of the district. The second case study is related to the territorial agri-environmental agreement experimented in Valdaso (Marche), where local farmers have adopted integrated pest management practices collectively with the aim of reducing the environmental impact of their farming practices. The analysis of these initiatives, carried out through participatory methods (Rapid Rural Appraisal), allowed developing a theoretical discussion on the role of innovative tools (such as co-production and co-management) in the provision of agri-environmental public goods. The case studies also provided some recommendations on the government intervention and policies needed to promote successful collective action for the provision of agri-environmental public goods. === La tesi si pone l’obiettivo di valutare il ruolo delle azioni collettive come una valida alternativa alle classiche forme di intervento in agricoltura, in particolare quelle volte ad incentivare la fornitura di beni pubblici ambientali. Quali sono i vantaggi delle azioni collettive, in termini di efficacia ed efficienza, rispetto alle classiche misure pubbliche o agli incentivi di mercato? Quali sono i drivers che spingono gli agricoltori a partecipare a progetti collettivi legati ai beni pubblici agro-ambientali? Attraverso quali strumenti di policy e quali assetti istituzionali è possibile favorire lo sviluppo di azioni collettive? Con l’obiettivo di rispondere a queste domande di ricerca, la tesi si articola su due livelli: un’analisi teorica sul ruolo delle azioni collettive nella fornitura dei beni pubblici e un’indagine specifica di due iniziative locali, dove si è sperimentato un approccio collettivo alla gestione delle risorse agro-ambientali. Il primo caso di studio riguarda il progetto denominato “Custodia del territorio”, sviluppato dall’ente gestore del comprensorio di Bonifica Media Valle del Serchio (Toscana), che prevede un accordo tra questo ente pubblico e gli agricoltori locali per la gestione idro-geologica del territorio in cui operano. Il secondo caso riguarda l’accordo agroambientale della Valdaso (Marche), dove gli agricoltori locali hanno adottato collettivamente pratiche di lotta integrata avanzata con l’obiettivo di ridurre l’impatto delle loro pratiche agricole sull’ambiente. L’analisi di queste iniziative, svolta attraverso metodologie partecipative (Rapid Rural Appraisal), ha permesso di sviluppate una riflessione teorica sul ruolo di strumenti innovativi (come co-produzione e co-gestione) alla gestione delle risorse agro-ambientali e di fornire raccomandazioni sul design e l’implementazione di politiche che possano favorire azioni collettive associate ai beni pubblici agro-ambientali.